Effectiveness of an eye movement desensitization and reprocessing intervention for the prevention of post- traumatic symptoms in perinatal loss: a randomized pilot controlled trial - Sureda-Caldentey, Bàrbara; Garcia-Gibert, Cristina; Martínez, Amparo; Giménez, Yolanda; Segú, Xavier; Mallorquí, Aida; Gelabert, Estel; Roca-Lecumberri, Alba; Torres-Giménez, Anna (Frontiers in Psychiatry, 2025)
BackgroundPerinatal loss is a situation with significant traumatic potential. However, no study has evaluated the effectiveness of eye movement desensitization and reprocessing (EMDR) for the prevention or treatment of post-traumatic symptoms in perinatal loss. The aim of this study was to assess the feasibility and preliminary effectiveness of an EMDR recent traumatic episode protocol (EMDR-RTEP) as a preventive intervention for post-traumatic symptoms after perinatal loss.Materials and methodsA one-site, open label, randomized controlled pilot trial was designed. A total of 40 women who had suffered perinatal loss in the Maternal-Fetal Medicine Service of a tertiary university hospital were recruited. The women were randomized to the EMDR-RTEP (n=20) or treatment as usual (TAU, n=20). Post-traumatic, depressive, anxiety and intensity of perinatal grief symptoms were assessed using standardized instruments at baseline and 3 months after perinatal loss (post-treatment). We performed an intention-to-treat analysis using analysis of covariance with baseline scores as covariates.ResultsWomen who received the EMDR-RTEP scored non-significantly lower than women who received TAU in all post-treatment outcomes. According to a satisfaction scale (CRES-4), women who received the EMDR-RTEP had a higher perceived emotional change than women who received TAU (U = 69.5, p = .011).ConclusionsEMDR-RTE is a feasible intervention, that is well accepted and tolerated by women after perinatal loss, with adequate satisfaction. Further studies with a larger sample size are needed to confirm these results.Clinical Trial Registrationhttps://www.clinicaltrials.gov/, identifier NCT05701137.